PENGEMBANGAN MODUL SINTAKSIS BERMODEL DISCOVERY LEARNING UNTUK MAHASISWA PENDIDIKAN BAHASA INDONESIA - Rohmah, Faizatur (Universitas Pendidikan Indonesia, 2020)
This study aims to (1) describe the process of syntax module development with the discovery learning model, and (2) describe the quality of a syntax module with the discovery learning models on a syntax material. This development model uses the ADDIE model (analysis, design, development, implementation, evaluation). The results of this study are (1) the process of the syntax module development designed through five stages, namely analysis, design, development, application, and evaluation; (2) the quality of the syntax module tested through the criteria of validity, practicality, and effectiveness. The validity data results are obtained from the expert validator assessment is of category very valid. The effectiveness data of student activities is of category good, the activity of the lecturers is of category very good, and the completeness of student learning is complete. The practicality data obtained from the assessment of the implementation of RPS is of category very good, student responses, and lecturer responses are of category positive.